2014
DOI: 10.1128/jvi.01814-14
|View full text |Cite
|
Sign up to set email alerts
|

Intrabronchial Infection of Rhesus Macaques with Simian Varicella Virus Results in a Robust Immune Response in the Lungs

Abstract: Varicella-zoster virus (VZV) is the etiological agent of varicella (chickenpox) and herpes zoster (shingles). Primary VZV infection is believed to occur via the inhalation of virus either in respiratory droplets or from shedding varicella lesions or by direct contact with infectious vesicular fluid. However, the ensuing immune response in the lungs remains incompletely understood. We have shown that intrabronchial inoculation of rhesus macaques with simian varicella virus (SVV), a homolog of VZV, recapitulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 80 publications
6
30
0
Order By: Relevance
“…Previous studies have shown a role for T cells in VZV and SVV dissemination (14,28,29). To determine whether T cells infiltrate the ganglia early after SVV infection in rhesus macaques, we digested DRG-T, DRG-C, and DRG-LS collected 3, 7, 10, 14, and 100 dpi and analyzed the isolated lymphocytes using flow cytometry and antibodies directed against CD4, CD8, CD28, CD95, and CCR7 in order to delineate naive and memory T cell subsets as well as CD20, CD27, and IgD to delineate naive and memory B cell subsets as recently described (19). Both CD4 and CD8 T cells were detected 3 to 14 dpi (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown a role for T cells in VZV and SVV dissemination (14,28,29). To determine whether T cells infiltrate the ganglia early after SVV infection in rhesus macaques, we digested DRG-T, DRG-C, and DRG-LS collected 3, 7, 10, 14, and 100 dpi and analyzed the isolated lymphocytes using flow cytometry and antibodies directed against CD4, CD8, CD28, CD95, and CCR7 in order to delineate naive and memory T cell subsets as well as CD20, CD27, and IgD to delineate naive and memory B cell subsets as recently described (19). Both CD4 and CD8 T cells were detected 3 to 14 dpi (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were pelleted at 2,000 rpm for 5 min and then resuspended in 30% Percoll gradient and spun for 15 min at 2,000 rpm to isolate mononuclear cells. Cells were then stained with antibodies directed against surface markers: CD4 (Tonbo Biosciences, San Diego, CA), CD8␤ (Beckman Coulter, Brea, CA), CD28 (Tonbo Biosciences), CD95 (BioLegend, San Diego, CA), and CCR7 (BD Pharmingen, San Diego, CA) to delineate naive and memory T cell subsets, as well as CD20 (Southern Biotech, Birmingham, AL), IgD (Southern Biotech, Birmingham, AL), and CD27 (BioLegend) to delineate B cell subsets as previously described (19). Samples were analyzed using the LSRII instrument (Becton, Dickinson and Company, San Jose, CA) and FlowJo software (TreeStar, Ashland, OR).…”
Section: Methodsmentioning
confidence: 99%
“…IL-6, IL-12, and IFNg levels peaked at 28 (IL-6), 14 (IL-12), and 21 (IFNg) dpi (data not shown). Given the observed changes in cytokines and chemokines, we next determined changes in frequency of dendritic cells (DCs) and monocytes in BAL, as recently described (14). In the BAL, the highest (22060) and middle (28493) dose animals showed an increase in DCs at 42 dpi, and all three animals showed changes in monocyte frequency at 42-56 dpi ( Figures 1E and 1F).…”
Section: Inflammation and Increased Frequency Of Dendritic Cells And mentioning
confidence: 99%
“…Innate immune cell populations were identified as described previously (14). To measure T and B cell frequency and proliferation, peripheral blood mononuclear cells (PBMC) and BAL cells were first stained with anti-CD4 (Tonbo Biosciences, San Diego, CA), CD8b (Beckman Coulter, Brea, CA), CD20 (BioLegend, San Diego, CA), IgD (Southern Biotech, Birmingham, AL), and CD27 (Tonbo Biosciences), then fixed and permeabilized before staining with anti-Ki67 (BD Pharmingen, San Diego, CA).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Nonhuman primates experimentally infected with simian varicella virus (SVV), the counterpart of VZV, produce IFN-␥ 7 to 11 days postinfection (dpi) (5,6). IFN-␥ also inhibits herpes simplex virus 1 (HSV-1) infection in vitro (7) and in vivo (8)(9)(10).…”
mentioning
confidence: 99%